DUALISME KEWENANGAN PEMBENTUKAN HUKUM DI BIDANG DESA - Riza Multazam Luthfy; Dhiya'ul Haq, Muhammad Imam (JURNAL SULTAN: Riset Hukum Tata Negara, 2024)
This study aims to examine the overlapping authority between the Ministry of Home Affairs and the Ministry of Village and Development of Disadvantaged Regions, Transmigration and Ministerial Regulations issued can disrupt the constitutional system of the Republic of Indonesia, especially related to the system and hierarchy of applicable laws and regulations. At the local level, such conditions create difficulties for village governments as technical implementers of policies issued by several ministries at once. The conflict between Ministerial Regulation norms and PDTT Amendments makes village governments as stakeholders feel confused about which laws and regulations will be used as guidelines. The type of research used is normative juridical research with a conceptual approach. The results obtained are based on the perspective of legal politics and legal harmonization analyses of two things. First, overlapping authorities and ministerial regulations occur because the Ministry of Home Affairs and the Ministry of Village Affairs have different perceptions about who has more authority to manage village affairs. Second, harmonization of the law of the Ministerial regulation that regulates villages can be realized through the political law of amending Law Number 6 of 2014 concerning Villages and the issuance of a new Presidential Regulation that specifies that there is only one ministry that handles villages. In this context, the author considers that village affairs should be more appropriately under the authority of the Ministry of Villages and Development of Disadvantaged Regions, Transmigration.